2021
DOI: 10.1016/j.heliyon.2021.e06406
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric analysis of micro electro mechanical system energy harvester research

Abstract: Micro Electro Mechanical System (MEMS) energy harvester's research interests have been increasing rapidly, indicating that the topic has given significant contributions to the sustainable development of energy alternatives. Although many research activities have been conducted and reported since several years ago, only limited efforts have been made to analyze the research's impact in this area. In this paper, we report a bibliometric analysis on the research progress in MEMS for energy harvester. VOSviewer so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 43 publications
0
14
0
1
Order By: Relevance
“…The recurrence of references to explicit authors and articles can be utilized to quantify whether distributions and examination affect the writing. This can be discovered by utilizing the VOSviewer programming with a comparable strategy, yet for this situation, the node type is changed to "Cited Author" to check for co-reference relations in the dataset ( Hamidah et al., 2021 ; Shi and Li, 2019 ). The top 25 authors cited to are recorded in Table 3 , and visualized cluster relationships are shown in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The recurrence of references to explicit authors and articles can be utilized to quantify whether distributions and examination affect the writing. This can be discovered by utilizing the VOSviewer programming with a comparable strategy, yet for this situation, the node type is changed to "Cited Author" to check for co-reference relations in the dataset ( Hamidah et al., 2021 ; Shi and Li, 2019 ). The top 25 authors cited to are recorded in Table 3 , and visualized cluster relationships are shown in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Color also shows the relationship or relationship between keywords. The circle size shows a positive relationship between the occurrence of keywords in the title and abstract [20]. Therefore, the size of letters and circles is determined by the frequency with which they occur.…”
Section: Literatur Reviewmentioning
confidence: 99%
“…In the analytic revolution in a certain research field, the bibliometric analysis is a powerful and effective approach, rather than a critical review on PMEH giving a clear overview of the global developments [12,13]. Bibliometrics is a research method for analyzing a material quantitatively in a research subject.…”
Section: Introductionmentioning
confidence: 99%